2017
DOI: 10.1007/s00382-017-3927-z
|View full text |Cite
|
Sign up to set email alerts
|

Observed changes in temperature extremes over Asia and their attribution

Abstract: indices, indicating the robustness of the warming signal as well as the attribution of warming to external causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 39 publications
9
48
0
1
Order By: Relevance
“…These results indicate a good agreement between the observations and the forced responses of the models for the intensity of warm extremes and underestimation by model simulations for the intensity of cold extremes. These results are similar to the detection results of the intensity indices in other regions , Kim et al 2016, Yin et al 2017, Dong et al 2018.…”
Section: Detection Resultssupporting
confidence: 89%
“…These results indicate a good agreement between the observations and the forced responses of the models for the intensity of warm extremes and underestimation by model simulations for the intensity of cold extremes. These results are similar to the detection results of the intensity indices in other regions , Kim et al 2016, Yin et al 2017, Dong et al 2018.…”
Section: Detection Resultssupporting
confidence: 89%
“…The studies show that CMIP3 and CMIP5 models generally reproduced the observed changes in temperature extremes in the second half of the 20th century at the global scale (Sillmann et al 2013, Flato et al 2013 and regional scale in some regions (e.g. Alexander and Arblaster 2009, Morak et al 2013, Dong et al 2018. Evidence has shown that anthropogenic forcing has very likely contributed to the observed changes in the frequency of daily temperature extremes since the 1950s (e.g.…”
Section: Introductionmentioning
confidence: 90%
“…The World Meteorological Organization (WMO) Expert Team on Climate Change Detection and Indices (ETCCDI) defined a set of indices to describe changes in temperature and precipitation extremes (Zhang et al 2011). These indices, computed from observational data of different regions, show increasing number of warm extremes and decreasing number of cold extremes in past decades over global land (Donat et al 2013a, 2013b, 2016, Alexander 2016) and over continents including Asia (Dong et al 2018), Europe (Christidis and Stott 2016), Australia (Alexander and Arblaster 2017) and other continents (Donat et al 2013b, Alexander 2016. These studies also suggest that changes in nighttime indices are larger than those in daytime indices.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, the number of archived and easily obtainable station normals is far greater than that of station time series, particularly as one goes back in time, thus maximizing available station data in space and time (New et al 1999(New et al , 2000. The data set has been widely used to quantify temperature extremes over China and other regions (Cao et al 2017, Dong et al 2018, Yin and Sun 2018. For the purpose of comparing temperature extremes in different regions of China, we divided the Chinese mainland into eight climate regions based on administrative divisions and the regional characteristics of the monsoon climate of China (Shi and Xu 2007, Mao et al 2010.…”
Section: Datamentioning
confidence: 99%